If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8u + -19 = -5u + 11 Reorder the terms: -19 + -8u = -5u + 11 Reorder the terms: -19 + -8u = 11 + -5u Solving -19 + -8u = 11 + -5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '5u' to each side of the equation. -19 + -8u + 5u = 11 + -5u + 5u Combine like terms: -8u + 5u = -3u -19 + -3u = 11 + -5u + 5u Combine like terms: -5u + 5u = 0 -19 + -3u = 11 + 0 -19 + -3u = 11 Add '19' to each side of the equation. -19 + 19 + -3u = 11 + 19 Combine like terms: -19 + 19 = 0 0 + -3u = 11 + 19 -3u = 11 + 19 Combine like terms: 11 + 19 = 30 -3u = 30 Divide each side by '-3'. u = -10 Simplifying u = -10
| t(4)=32 | | 2v-15=7v-5 | | 2=1.16x+x | | -7v-4=4v+18 | | 2z+20=5z-7 | | e^3=5-2x | | 5w-7=9w+9 | | 3(4x+4)+(-50x)-9(-8-x)= | | 2w-14=7w+1 | | 5x2/3-3x1/3 | | 2w+3=4w+2 | | 1/2(x-4)=2(x+2) | | -9v-4=-v-12 | | 2x^2-19+9=0 | | 4t-18=-t-13 | | 4t-18=-3-13 | | 4b+5=19 | | 9v+19=7v+5 | | 5m+m=132 | | 4z-3=-3z-3 | | x-8.6=3.2 | | 10-7lnx=-4 | | r-7/9=20/9 | | u/3-10=-14 | | 3x(x+7)=36 | | 9+24=3x | | 2x^3+x^2+7=-3 | | (2x^2y^3)^2(-4x^4)^3/(xy)4x^6y^3)^4 | | 15/55 | | 3x+4y+5x-3y= | | g(x)=4x^2-48x+7 | | 23+x=11 |